Modelowanie własności szeregów stóp zwrotu - skośność rozkładów - Piontek, Krzysztof (Modelling of financial time series characteristics - skewness of distributions, 2005)
It is observed that the following effects occur in financial time series of returns of stock market indices: autocorrelation of returns, fat tails of return distributions, volatility clustering, leverage effect and skewness. The article presents a method of describing above mentioned features by means of various generalisations of ARCH model. Main attention was devoted to the problem of skewness of stock return distributions. Two possible (for use with GARCH models) skew distributions, which are based at well-known (-Student distributions, are presented. In the empirical part of the paper models for some stocks from Polish market are investigated. The results can be applied to risk measuring with Value at Risk method or portfolio selection.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 297-308